THE THE EFFECT OF THE HISTORICAL THINKING APPROACH ON STUDENTS’ CRITICAL THINKING SKILLS IN HISTORY LEARNING AT SMAN 1 RONGGA - Tedi Sutisna; Jajang Hendar Hendrawan; Ernandia Pandikar (SOSIOEDUKASI, 2026)
This study was motivated by the dominance of memorization-oriented history instruction, which has limited the optimal development of students’ critical thinking skills. The purpose of this study was to analyze the effect of the historical thinking approach on students’ critical thinking skills in history learning at SMAN 1 Rongga. The conceptual framework was based on the relationship between three dimensions of historical thinking, namely Use of Primary Source Evidence, Cause and Consequence, and Historical Perspective-Taking, and four dimensions of critical thinking, namely interpretation, analysis, evaluation, and inference. This study employed a quantitative approach with a survey method. The sample consisted of 127 tenth-grade students selected through proportionate stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The findings revealed that the historical thinking approach had a significant simultaneous effect on students’ critical thinking skills, as indicated by an F value of 211.270 and a significance value of <0.001. The Adjusted R Square value of 0.834 indicated that 83.4% of the variation in students’ critical thinking skills could be explained by the three dimensions of historical thinking. Partially, Cause and Consequence and Historical Perspective-Taking had positive and significant effects, while Use of Primary Source Evidence did not have a significant effect. The most dominant dimension was Historical Perspective-Taking. Therefore, the historical thinking approach is appropriate to be applied as a history learning strategy to develop students’ critical thinking skills.